Photonic gel film with controllable water seepage and color change and double-layer hollow structure as well as preparation method and application of photonic gel film

Through the photonic gel film with a double-layer hollow structure, the coordinated regulation of three-dimensional photonic crystals and polymers is used to solve the stability and durability of existing controllable water-permeable color changes and efficient application, and is applicable in various scenarios.

CN119247639AActive Publication Date: 2025-01-03GUANGDONG LABORATORY OF CHEMISTRY & FINE CHEMICAL IND JIEYANG CENTER JIEYANG +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411306131.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Existing controlled water-permeable discoloration materials have stability and durability problems in long-term use, and rely on reaction discoloration to cause environmental damage, lack of stable and reversible discoloration mechanisms and efficient contrast of color change.

Method used

The photonic gel film adopts a double-layer hollow structure, consisting of three-dimensional photonic crystals and polymers. By regulating the photonic crystal structure, polymer cross-linking degree and hydrophilicity, controllable color changes are achieved. The preparation method includes polystyrene- The combination of silica core-shell structure and anti-opal gel forms a slow water infiltration process and a dual water seepage mechanism.

Benefits of technology

It realizes controllable color changes, improves the stability and durability of the material, and is suitable for indoor ski resort snow melt warning, alcohol detection and high-level anti-counterfeiting labels, providing better time indication functions and fast reversible information encryption and decryption capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite material preparation, and discloses a water-seepage-controllable color-changing photonic gel film with a double-layer hollow structure and a preparation method and application thereof. The method comprises the following steps: preparing a three-dimensional PS-SiO2 photonic crystal and a three-dimensional SiO2 photonic crystal; calcining the three-dimensional PS-SiO2 photonic crystal at a high temperature, filling a polymer, performing ultraviolet exposure curing to obtain hollow SiO2 structural color gel, performing ultraviolet exposure curing on the three-dimensional SiO2 photonic crystal filled polymer, and performing etching with hydrofluoric acid to obtain inverse opal gel; and bonding the hollow SiO2 structural color gel and the inverse opal gel up and down to obtain the photonic gel film with the controllable water seepage and color change double-layer hollow structure. The photon gel film can be applied to a signal indicator for snow melting warning of a large ski field, a portable alcohol solubility detector or an anti-counterfeiting identification label of a small commercial package.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite material preparation, and particularly relates to a photonic gel film with a double-layer hollow structure capable of controllable water permeation and color change, and a preparation method and application thereof. Background Art

[0002] Controllable water-permeable color-changing materials are a type of smart material that has the ability to adaptively respond to environmental changes. For example, by introducing components that react to liquid penetration (such as color-changing agents or sensitive compounds), these materials can undergo significant color changes when encountering liquids. However, the long-term use of color-changing agents or sensitive compounds can cause damage to the environment, and also faces many material research and development issues, including achieving a stable and reversible color-changing mechanism, enhancing the contrast of color changes, and improving the stability and durability of materials.

[0003] Therefore, developing structural colors that do not rely on reaction color change and can continuously and reversibly change color is undoubtedly a preferred mode. Among them, three-dimensional hollow photonic crystals have attracted widespread attention due to their large pore structure. According to Bragg's law The diffraction wavelength λ can be adjusted by n eff to change, where λ is the diffraction wavelength, n eff is the effective refractive index, d is the distance between particles, and θ is the measured angle relative to the vector perpendicular to the close-packed plane. This structure of periodic appearance of low-refractive index materials in high-refractive index materials is the basic feature of color change. At the same time, the hollow structure can accommodate a variety of liquids with different refractive indices to achieve a variety of color changes. Compared with the color change behavior of the current single hollow photonic structure, the preparation and performance development of the complex double-layer hollow structure of the controllable water permeable film is undoubtedly more variable and practical.

[0004] Therefore, the research on controllable water-permeable color-changing materials aims to improve the efficiency and accuracy in fields such as information recognition and liquid detection, and to improve the safety and reliability of application scenarios through the intelligent response of materials. The research on such materials not only promotes the development of intelligent sensing technology, but also promotes innovation in fields such as high-performance optical materials and environmental monitoring equipment. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for preparing a photonic gel film with a double-layer hollow structure and controllable water permeation and color change.

[0006] Another object of the present invention is to provide a double-layer hollow structure photonic gel film with controllable water permeability and color change prepared by the above-mentioned preparation method; the prepared photonic gel film is composed of three-dimensional photonic crystals and polymers, wherein the three-dimensional photonic crystals can use but are not limited to polystyrene-silica core-shell structure balls or monodisperse silica microspheres; wherein the polymer can use but is not limited to polyacrylic acid, polyhydroxyethyl methacrylate, polyethylene glycol diacrylate polymer and polymethyl acrylate.

[0007] The present invention achieves controllable color change by means of coordinating the water permeability of various photonic crystals and polymers; these methods include coordinating the three-dimensional photonic crystal structure, the degree of polymer cross-linking, and the degree of polymer hydrophilicity to coordinately control the process of structural color change.

[0008] Another object of the present invention is to provide an application of the above-mentioned double-layer hollow structure photonic gel film with controllable water permeation and color change; the photonic gel film can be applied to the following aspects: 1. Used as a signal indicator for snow melting warning in indoor ski resorts; 2. Used as a portable alcohol concentration detector; 3. Used as a small commercial packaging anti-counterfeiting label for hiding information.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a double-layer hollow photonic gel film with controllable water permeation and color change, comprising the following steps:

[0011] (1) initiating a polymerization reaction between styrene and an initiator at 60 to 80° C. to obtain polystyrene microspheres; reacting the obtained polystyrene microspheres with ammonia water and vinyl triethoxysiloxane to obtain polystyrene-silica core-shell nano-microspheres with polystyrene as the core and silica as the shell;

[0012] The thickness of the outer shell silica of the polystyrene-silica core-shell nanospheres is 19-60 nm, and the thickness is regulated by changing the volume ratio of ammonia water to vinyl triethoxysiloxane, wherein the volume ratio of ammonia water to vinyl triethoxysiloxane is (1.2-10): (0.45-3.75);

[0013] The polystyrene-silica core-shell microspheres are dispersed in an ethanol solvent, and then the polystyrene-silica core-shell nano-microspheres are assembled into neat face-centered cubic three-dimensional PS-SiO2 photonic crystals by self-assembly through evaporation of the ethanol solvent.

[0014] (2) tetraethyl orthosilicate is autonomously nucleated and grown at room temperature under the action of ammonia water to obtain solid silica nanostructured microspheres; the particle size of the solid silica nanostructured microspheres is 180-260 nm, and the particle size is controlled by changing the volume ratio of ammonia water to tetraethyl orthosilicate, and the volume ratio of ammonia water to tetraethyl orthosilicate is (4-7.5):20;

[0015] The solid silica nanostructured microspheres are dispersed in an ethanol solvent, and then the ethanol solvent is evaporated to self-assemble the solid silica nanostructured microspheres into a three-dimensional SiO2 photonic crystal with neat face-centered cubic stacking;

[0016] (3) calcining the three-dimensional PS-SiO2 photonic crystal obtained in step (1) at 500-600° C. in a muffle furnace for 8-12 h to obtain a hollow SiO2 photonic crystal; filling the prepolymer monomer added with a photoinitiator into the hollow SiO2 photonic crystal, curing by ultraviolet exposure, embedding and combining the prepolymer monomer and the hollow SiO2 photonic crystal, and peeling off the obtained polymer film to obtain a hollow SiO2 structural color gel;

[0017] (4) filling the prepolymer monomer added with a photoinitiator into the three-dimensional SiO2 photonic crystal obtained in step (2), curing by ultraviolet exposure, inlaying and combining the prepolymer monomer and the three-dimensional SiO2 photonic crystal, peeling off the obtained polymer film, and etching SiO2 with hydrofluoric acid having a volume percentage concentration of 4% to obtain an inverse opal gel;

[0018] (5) The hollow SiO2 structural color gel obtained in step (3) and the inverse opal gel obtained in step (4) are stacked together in two layers, and bonded under ultraviolet light using ethoxylated trimethylolpropane triacrylate and a photoinitiator in a mass ratio of 99:1 to obtain a double-layer hollow structure photonic gel film with controllable water permeability and color change.

[0019] The initiator in step (1) is potassium persulfate or ammonium persulfate.

[0020] The thickness of the silica in the shell in step (1) is the key to controlling the water permeability in the first step, and the thickness of the silica is achieved by controlling the combined ratio of ammonia water and vinyl triethoxysiloxane. The thinner the silica in the shell, the shorter the water permeation process and the stronger the water permeability. Conversely, the thicker the shell, the longer the water permeation process and the weaker the water permeability.

[0021] In step (1), the three-dimensional PS-SiO2 photonic crystal is prepared by ultraviolet lithography to form a variety of but not limited pattern labels such as "Chinese knot", "QR code" and other patterns, and then the subsequent steps are carried out.

[0022] The calcination time in step (2) is 550° C. and the calcination time is 12 hours.

[0023] The prepolymer monomers in step (3) and step (4) are composed of polymer monomers and crosslinking agents in a mass ratio of 1:1 to 1:2. The polymer monomers are one or more of acrylic acid, hydroxyethyl methacrylate, polyethylene glycol diacrylate and methyl acrylate, and are arranged from strong to weak according to hydrophilicity: acrylic acid>hydroxyethyl methacrylate>polyethylene glycol diacrylate>methyl acrylate. The different water permeability of the gel can be regulated, which is a means of controlling the water permeability in the second step. The crosslinking agent is ethoxylated trimethylolpropane triacrylate. Preferably, the prepolymer monomers include acrylic acid, polyethylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate in a mass ratio of 1:4:5 to 1:4:10, and increasing and decreasing the content of the crosslinking agent is a means of controlling the water permeability in the third step.

[0024] The photoinitiator in step (3) and step (4) is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the amount of the photoinitiator used is 2% to 3% of the mass of the polymer monomer in the prepolymer liquid monomer.

[0025] A photonic gel film with a double-layer hollow structure and controllable water permeation and color change is prepared by the above preparation method.

[0026] The above-mentioned double-layer hollow structure photonic gel film with controllable water permeation and color change is used in signal indicators for snow melting warnings in large ski resorts, portable alcohol solubility detectors, or anti-counterfeiting identification labels for small commercial packages.

[0027] The above-mentioned double-layer hollow structural color gel with controllable water seepage and color change is used as a signal indicator for snowmelt warning in large ski resorts. It is characterized in that the snowmelt produces accumulated water, which causes the color of the structural color gel to change, and the snowmelt time can be judged based on the different color labels.

[0028] The above-mentioned double-layer hollow structural color gel with controllable water permeation color change is used for a portable alcohol solubility detector, which is characterized by: a series of commercially available alcohol-containing products of a certain brand are dripped on the structural color gel, and different display effects are displayed for different alcohol colors;

[0029] The above-mentioned double-layer hollow structural color gel with controllable water permeability and color change is used for the application of optical anti-counterfeiting identification marks for small commercial packaging labels. It is characterized by: the hidden commercial anti-counterfeiting code information is displayed when it is wet and transparent, and solvents of different concentrations can be used as responsive encoding means.

[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0031] The present invention proposes a new method for regulating the photonic bandgap (PBG) during a slow water infiltration process. The non-sensitive structural color indicator label of slow infiltration makes it possible to determine the time of the change response. Based on the premise of the existence of a stable periodic arrangement structure of hollow SiO2, the material has a synergistic water penetration effect affected by the three factors of SiO2 thickness, gel hydrophilicity and gel cross-linking degree. Importantly, the larger SiO2 thickness makes the water penetration process slower. The more hydrophilic the gel and the lower the cross-linking degree of the gel, the faster the water penetration trend, and vice versa. Furthermore, the macroporous structure of the inverse opal gel is combined with the hollow SiO2 to obtain a new double-layer hollow structural color gel. This structural feature combines the dual water penetration mechanism of hollow SiO2 and inverse opal at the same time, and is effectively used in large places such as indoor ski resorts and ice storages for early warning reminders of ice melting control. Obviously, the Bragg diffraction effect accompanied by slow penetration can provide a better time indication function. In addition, by using solvents with low surface tension, such as ethanol and water, high-level anti-counterfeiting labels can achieve fast and reversible information encryption and decryption, playing a good role in protecting high-value goods and combating counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the preparation process of hollow structural color gel with controllable water permeation color change;

[0033] Figure 2 The QR code patterns of hollow SiO2 photonic crystals are colorless dry state, blue ethanol wet state (a), dry purple state, green ethanol wet state (b), colorless dry state with different SiO2 thickness, blue ethanol wet state (c), dry green state, orange ethanol wet state (d);

[0034] Figure 3 Digital photos of the structural color changes of four hollow SiO2 photonic crystal gels at different angles;

[0035] Figure 4 The actual pictures of structural colors of hollow SiO2 photonic crystals at different water infiltration stages (time dependence);

[0036] Figure 5 The structural color reflection spectrum of the hollow SiO2 photonic crystal immersed for 3 hours;

[0037] Figure 6 The schematic diagram of the structural color change of the double-layer hollow structural color gel when immersed in water and ethanol, as well as the schematic process of hiding when dry and showing when wet;

[0038] Figure 7 Video contact angle test of inverse opal gel, corresponding to the contact angle values ​​under pure water, 5%, 10%, 15%, and 20% volume fraction alcohol concentrations;

[0039] Figure 8 A schematic diagram of the principle and process of a signal indicator for warning of snowmelt applied in large ski resorts;

[0040] Fig. 9 This is a picture of the structural color display of the double-layer hollow structural color gel used in testing 3°, 5°, and 8° commercially available edible alcoholic beverages;

[0041] Fig.10 Ethanol concentration-dependent information display process applied in high-level encrypted anti-counterfeiting labels. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0043] The preparation process of one of the following embodiments ( Figure 1 ), the specific steps are as follows:

[0044] Step 1: Monodisperse polystyrene (PS) nanospheres are added to a reaction solution of mixed ammonia water and vinyl triethoxysilane at a certain dispersion concentration of 3-5 mL. According to the volume ratio of ammonia water + vinyl triethoxysilane (1.2-10): (0.45-3.75), SiO2 thicknesses ranging from 19 nm to 60 nm can be obtained. After the reaction is completed, polystyrene-silica (PS-SiO2) core-shell structure microspheres of different particle sizes are obtained; the microspheres are dispersed in an ethanol solvent, and then the ethanol solvent is evaporated and self-assembled to assemble the polystyrene-silica core-shell nanospheres into neat face-centered cubic stacked three-dimensional PS-SiO2 photonic crystals;

[0045] Step 2: Add ammonia water + tetraethyl orthosilicate in a volume ratio of (4-7.5):20 to a pure water and ethanol system to obtain solid SiO2 nanostructured microspheres ranging from 180 to 260 nm; disperse the solid silica nanostructured microspheres in an ethanol solvent, and then use the ethanol solvent to evaporate and self-assemble to assemble the solid silica nanostructured microspheres into a three-dimensional SiO2 photonic crystal with neat face-centered cubic stacking; the solvent (ethanol) evaporates and self-assembles to assemble the solid SiO2 into a three-dimensional photonic crystal with neat face-centered cubic stacking;

[0046] Step 3: The three-dimensional PS-SiO2 photonic crystal obtained in step 1 is fully calcined at a high temperature of 500-600°C for 8-12h to obtain a hollow SiO2 photonic crystal, and a prepolymer monomer of acrylic acid, polyethylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate (with an additional photoinitiator of 2-3 v / v%) in a mass ratio of 1:4:5-1:4:10 is filled into the hollow SiO2 photonic crystal, and cured by ultraviolet exposure. The prepolymer monomer and the hollow SiO2 photonic crystal are inlaid and combined, wherein the same color polymer material can be obtained by replacing acrylic acid with an equal volume of hydroxyethyl methacrylate or methyl acrylate. The obtained polymer film is peeled off and taken out to obtain a hollow SiO2 structural color gel;

[0047] Step 4: In the same manner as step 3, a prepolymer monomer of acrylic acid, polyethylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate (with an additional photoinitiator of 2 to 3 v / v%) in a mass ratio of 1:4:5 to 1:4:10 is filled into the three-dimensional SiO2 photonic crystal obtained in step 2, and cured by ultraviolet exposure. The prepolymer monomer and the three-dimensional SiO2 photonic crystal are inlaid and combined. The filling of the prepolymer monomer is the same as step 3. The obtained polymer film is peeled off and taken out, and SiO2 is etched with hydrofluoric acid at a volume percentage concentration of 4% to obtain an inverse opal gel;

[0048] Step 5: Stack the hollow SiO2 structural color gel obtained in step 3 and the inverse opal gel obtained in step 4 together in two layers, and bond them under ultraviolet light using ethoxylated trimethylolpropane triacrylate and photoinitiator in a mass ratio of 99:1 to obtain a double-layer hollow structure photonic gel film with controllable water permeability and color change.

[0049] The photonic gel film with a double-layer hollow structure and controllable water permeation color change prepared by the present invention has a structural feature that combines the dual water permeation mechanism of the hollow SiO2 structural color gel and the inverse opal, and is effectively used in large places such as indoor ski resorts and ice storages to provide early warning reminders for ice melting control. In addition, by using solvents with low surface tension, such as ethanol and water, high-level anti-counterfeiting labels can achieve fast and reversible information encryption and decryption, playing a good role in protecting high-value goods and combating counterfeiting.

[0050] Example 1

[0051] This embodiment provides a method for preparing polystyrene (PS) and polystyrene (PS)-silicon dioxide (SiO2) photonic crystals, comprising the following steps:

[0052] Step 1: Styrene monomer is mixed with water under the emulsification of sodium dodecyl sulfate to form a suspension, the amount of styrene is 10-15g, preferably 15g, and the amount of sodium dodecyl sulfate is 80-120mg, and different addition amounts are selected according to different particle sizes. The experiment designs three particle size ranges of PS, namely 180nm, 200nm and 220nm, corresponding to the amount of sodium dodecyl sulfate of 85mg, 100mg and 115mg, respectively. Finally, persulfate is used to start the polymerization reaction under the action of thermal initiation to obtain polystyrene (PS).

[0053] Step 2: Add the 180nmPS and 220nmPS reaction stock solutions obtained by the reaction to new deionized water, preferably in an amount of 3-5mL, and then add a combination of 1.2mL+0.45mL~10mL+3.75mL of ammonia water (NH3·H2O)+vinyl triethoxysiloxane (TEOVS) in a mixed solvent of PS and deionized water, and react for 3-5h.

[0054] Step 3: Place the reaction solution in a centrifuge tube for centrifugal drying. Disperse the solid obtained by ultrasonication in anhydrous ethanol to form a dispersion (the dispersion concentration is preferably 1% by mass volume). Then, insert a glass bottle into the dispersion and place it in a constant temperature and humidity environment for 3 days to obtain a PS-SiO2 photonic crystal.

[0055] Example 2

[0056] This embodiment provides a method for preparing a hollow SiO2 photonic crystal with a two-dimensional code pattern of different colors, comprising the following steps:

[0057] Step 1: According to the various PS-SiO2 photonic crystals obtained in Example 1, they are labeled as 180nm-NH3·H2O4 according to the experimental formula mL +TEOVS 1.5 mL , 180nm-NH3·H2O6 mL +TEOVS 2.25mL or 220nm-NH3·H2O2 mL +TEOVS 0.75 mL , 220nm-NH3·H2O6 mL +TEOVS 2.25 mL Four PS-SiO2 photonic crystals with different core-shell ratios are represented.

[0058] Step 2: Place the above PS-SiO2 photonic crystals at 500-600℃ and heat for 8-12h to preliminarily obtain hollow SiO2 photonic crystals. Adjust the heating time to obtain hollow SiO2 with different residual carbon amounts, preferably heating at 550℃ for 8h.

[0059] Step 3: Prepare a negative photoresist with a combination ratio of 99:1 by mass. Experimentally weigh ethoxylated trimethylolpropane triacrylate and 2-hydroxy-2-methyl-1-phenyl-1-propanone, mix them by ultrasonication to obtain a prepolymer solution that can be used in the UV lithography process.

[0060] Step 4: Fill the negative photoresist in the glass interlayer with a spacing of 0.14 cm, fully penetrate the PS-SiO2 photonic crystal, and then use a black pattern baffle to cover the top of the glass sheet and irradiate with ultraviolet light. The ultraviolet exposure time is set to 3 to 5 seconds according to different ultraviolet lamp powers.

[0061] Step 5: Use anhydrous ethanol to rinse the unpolymerized liquid, and use a surgical blade to remove the photoresist, leaving behind hollow silica with a pattern (such as a QR code). Depending on the size of the photonic crystal, it has different colors under ethanol rinsing.

[0062] Experimental results: Figure 2 As shown, 180nm-NH3·H2O4 mL +TEOVS 1.5 mL The obtained colorless photonic crystals showed blue color when wetted with ethanol ( Figure 2 a); 180nm-NH3·H2O6 mL +TEOVS 2.25 mL The purple photonic crystals were obtained, and they showed green color when wetted with ethanol ( Figure 2 b); 220nm-NH3·H2O 2mL +TEOVS 0.75 mL Colorless photonic crystals were obtained, and blue was obtained when wetted with ethanol, but Figure 2 The difference is that the hollow silica here is thinner and has stronger water permeability ( Figure 2 c); 220nm-NH3·H2O 6mL +TEOVS 2.25 mL The green photonic crystals were obtained, and they showed orange color when wetted with ethanol ( Figure 2 d); the QR code pattern changes to different colors in the dry state and when immersed in ethanol.

[0063] Example 3

[0064] This embodiment provides a method for preparing a hollow SiO2 photonic crystal with a Chinese knot pattern and angle-dependent color change, comprising the following steps:

[0065] Step 1: The PS-SiO2 photonic crystals are treated by the preparation method in Example 2. The difference is that the preparation of hollow SiO2 photonic crystals of different colors depends on the adjustment of the combination ratio of 1.2mL+0.45mL~10mL+3.75mL of ammonia water (NH3·H2O) + vinyl triethoxysiloxane (TEOVS). The purple photonic crystals are preferably prepared with 4mLNH3·H2O+1.5mLTEOVS formula (180nmPS), the blue photonic crystals are preferably prepared with 6mLNH3·H2O+2.25mLTEOVS formula (180nmPS), the green photonic crystals are preferably prepared with 4mLNH3·H2O+1.5mLTEOVS formula (220nmPS), and the orange photonic crystals are preferably prepared with 6mLNH3·H2O+2.25mLTEOVS formula (220nmPS).

[0066] Step 2: The same operation process of step 2, step 3 and step 4 described in Example 2 is adopted, except that the patterned photolithography template is replaced with a Chinese knot pattern.

[0067] Step 3: Use acrylic acid, polyethylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate prepolymer monomers in a mass ratio of 1:4:5 to 1:4:10 (plus photoinitiator 2 to 3 v / v%) to fill the hollow SiO2 photonic crystal, cure it by UV exposure and completely peel off the polymer film.

[0068] Experimental results: Figure 3 As shown, the 420-600 nm hollow SiO2 gel exhibits regular color change behavior at a change angle of 0 to 60°, purple-colorless, blue-purple, green-blue, and orange-green.

[0069] Example 4

[0070] This embodiment provides a test and judgment result of the water seepage process of a hollow SiO2 structural color gel, including the following steps:

[0071] Step 1: Preparation of hollow SiO2 photonic crystals as described in Example 3, preferably orange preparation scheme 6mL NH3·H2O formula (220nmPS).

[0072] Step 2: Prepare gel material with controllable water permeability. Experimentally prepare prepolymer solutions with different water permeability. Select polymerizable monomers such as acrylic acid, hydroxyethyl methacrylate, polyethylene glycol diacrylate, and methyl acrylate for the experiment. Through the comparison of water permeability test, it can be seen that the hydrophilic swelling ability from strong to weak is acrylic acid>hydroxyethyl methacrylate>polyethylene glycol diacrylate>methyl acrylate.

[0073] Step 3: The combination ratio is preferably a gel material with slow water permeability and certain anti-swelling performance. In actual comparison, three gels of acrylic acid copolymerized hydroxyethyl methacrylate, acrylic acid copolymerized polyethylene glycol diacrylate and acrylic acid copolymerized methyl acrylate were referenced. The comparison of any combination ratios preferably selected the combination ratio of acrylic acid and polyethylene glycol diacrylate and crosslinking agent ethoxylated trimethylolpropane triacrylate of 1:4:5 to 1:4:10 (mass ratio) (additional photoinitiator 2 to 3 v / v%) as the preferred combination ratio of the slow permeation gel.

[0074] Step 4: Through the measurement of portable fiber optic spectrometer, the experiment was designed to study the water permeation and structural color change process of hollow SiO2 structural color gel within 3 hours, and the influence of gel hydrophilicity and cross-linking degree on gel water permeability was measured by data comparison.

[0075] Experimental results: Filling orange hollow SiO2 photonic crystals with acrylic acid, polyethylene glycol diacrylate and crosslinker ethoxylated trimethylolpropane triacrylate prepolymer monomers in a mass ratio of 1:4:5 to 1:4:10 yields a gel that changes color slowly when it permeates water. This material has both a certain permeability and anti-swelling properties, and can change color over a long period of time. Using less hydrophilic hydroxyethyl methacrylate and methyl acrylate will greatly weaken the permeation process. Figure 4 As shown in the figure, as the water immersion process progresses, the original reflectance spectrum value of the gel is 643nm, and it also goes through an intermediate process of 688nm and reaches a stable result of 700nm. Figure 5 The structural color reflectance spectrum results after three hours of immersion also prove the occurrence of three processes.

[0076] Example 5

[0077] This embodiment provides a method for preparing a double-layer hollow structure color gel and a water seepage detection method, comprising the following steps:

[0078] Step 1: Preparation of inverse opal structure. First, ammonia water, tetraethyl orthosilicate and deionized water were dispersed in 200 mL of anhydrous ethanol in a mass ratio of 4:20:30 to 7.5:20:30, and then stirred at high speed for 90 seconds, and then reacted at a stirring speed of 300 rpm for 3 hours to synthesize monodispersed SiO2 nanoparticles. The SiO2 obtained in the experimental preparation was prepared into SiO2 photonic crystals using the same method as in step 3 of Example 1.

[0079] Step 2: Use the combination ratio of acrylic acid, polyethylene glycol diacrylate and ethoxylated trimethylolpropane triacrylate of 1:4:5 to 1:4:10 (mass ratio) (additional photoinitiator 2 to 3 v / v%) described in Example 4 to fill SiO2 photonic crystals and cure under ultraviolet light.

[0080] Step 3: Peel off the polymer film and soak it in a 4% (volume fraction) hydrofluoric acid solution for 5 hours. The experiment uses SiO2 with different particle sizes to obtain a variety of inverse opal gels with structural colors (such as purple, green and yellow).

[0081] Step 4: Combine the inverse opal gel obtained in step 3 with any of the hollow SiO2 gels in Example 2 and Example 3. Use ethoxylated trimethylolpropane triacrylate and photoinitiator at a ratio of 99:1 (mass ratio) for UV bonding, and apply it to water seepage identification in multiple scenarios.

[0082] Since the ratio of acrylic acid to polyethylene glycol diacrylate to ethoxylated trimethylolpropane triacrylate is 1:4:5 to 1:4:10, an inverse opal gel material having a hydrophilic contact angle of 30° at an ethanol concentration of 5% is obtained, Figure 6 The experimental results show that an anti-counterfeiting label with solvent-selective display and hiding functions has been successfully prepared. As the amount of ethoxylated trimethylolpropane triacrylate increases, the degree of gel crosslinking increases, and the structural color gel becomes stronger in terms of wet resistance to deformation. Since the water penetration process of the hollow structure of the inverse opal gel is related to the pore size and the surface tension of the penetration solution, when soaked in pure water, the structural color is usually a blurred change process, and when alcohol is added, it will quickly become transparent and show the pattern below.

[0083] Example 6

[0084] This embodiment provides a double-layer hollow structural color gel for use in a large ski resort snowmelt warning signal indicator, a portable alcohol solubility detector, and an anti-counterfeiting identification label for small commercial packaging, including the following instructions:

[0085] Application 1: Artificial ski resorts must maintain an indoor environment below -20℃. However, due to the influence of the temperature of the venue area and the indoor atmospheric pressure, partial melting of ice and snow is inevitable. Therefore, in order to better monitor the degree of ice and snow freezing in the venue to ensure a good consumption experience for skiers, we propose to use double-layer hollow structural color gel as an indicator to measure the degree of ice and snow melting, as a technical indicator of whether the snow in the venue needs a certain scale of maintenance ( Figure 8), and if inverse opal is used as an indicator, its water response speed is too fast, and it is impossible to judge whether maintenance is needed. In the conceptual diagram, a tag with an arbitrary pattern (Chinese knot in the figure) is placed in an area with high indoor temperature or low-lying area. As a color indicator for fixed-point monitoring, it can play a good role in judging whether the ice and snow have melted and how long the ice and snow have melted. First, the controllable infiltration tag is designed as 4 sets of parallel data. During each site indicator measurement, the staff needs to use a mobile phone to scan and read the tag. The optical image acquired by the camera is then quickly decomposed into an RGB image by the mobile phone. Each color point in the image is scanned and integrated, and then a set of RGB output values ​​for the structural color tag is obtained. The law of change of RGB values ​​over time is used to calculate the water penetration time. This can not only play a role in snow melting, but also avoid the trouble and inconvenience of spectral analysis of the specific penetration state of water.

[0086] Application 2: The wort concentration of beer is one of the important indicators to measure the quality of beer. It indicates the sugar content of the wort in the raw materials at the beginning of fermentation. Specifically, the wort concentration can be divided into three levels: 1. Low-concentration beer: the wort concentration is 6°-8°, and the alcohol content is also the lowest, generally around 2%; 2. Medium-concentration beer: the wort concentration is 10°-12°, and the alcohol content is around 3.5%. This is the main variety of mid-to-high-end industrial beer production in my country; 3. High-concentration beer: the wort concentration is 12°-20°, and the alcohol content is close to 5%. It is internationally recognized that beer above 12° is high-end beer. This type of beer has a long brewing cycle, is resistant to storage, and has a mellow taste. A double-layer hollow structural color gel is used as an indicator to distinguish between beers of different concentrations. By Figure 7 The hydrophilic contact angle is >30°, and the theoretical calculation shows that the neck angle of the inverse opal gel pore is 30°. When the alcohol concentration increases, the contact angle gradually decreases, proving that the solvent wettability is stronger. Fig. 9 As shown, a cocktail of the same brand sold on the market was used to test the alcohol concentration. The experimental results preliminarily proved that when the alcohol solubility was 3%, the hollow structure was not completely infiltrated and the structural color (yellow-green) did not disappear. When the alcohol solubility was 5%, the structural color (yellow-green) showed signs of disappearing. When the alcohol concentration was 8%, the structural color (yellow-green) completely disappeared and became colorless. Therefore, a portable alcohol solubility detector was proved to be effective.

[0087] Application three: QR code anti-counterfeiting technology is used to ensure the authenticity and integrity of goods or documents. Its main functions include: verifying authenticity, tracking and tracing, preventing tampering, and simplifying the verification process. The QR code can contain a unique identification code or information. By scanning the QR code, the user can verify whether the product is genuine and avoid purchasing fakes. Secondly, the QR code can record the production and transportation process of the product, help track the source and circulation path of the product, and increase the transparency of the supply chain. In terms of security performance, by encrypting or embedding digital signatures, the QR code can prevent information from being tampered with and ensure that the displayed information is consistent with the actual situation. Fig.10 As shown, the QR code anti-counterfeiting feature uses a transparent display authentication principle in the identification process, which can effectively prevent the theft and counterfeiting of the QR code. The anti-counterfeiting concept is hidden at the bottom of the fuzzy structural color of the inverse opal. The QR code can be selectively displayed by using solvent wetting. This strategy plays a key role in protecting product information and improving the level of security authentication.

[0088] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a double-layer hollow photonic gel film with controllable water permeation and color change, characterized in that The steps include: (1) initiating a polymerization reaction between styrene and an initiator at 60 to 80° C. to obtain polystyrene microspheres; reacting the obtained polystyrene microspheres with ammonia water and vinyl triethoxysiloxane to obtain polystyrene-silica core-shell nano-microspheres with polystyrene as the core and silica as the shell; The thickness of the outer shell silica of the polystyrene-silica core-shell nanospheres is 19-60 nm, and the thickness is regulated by changing the volume ratio of ammonia water to vinyl triethoxysiloxane, wherein the volume ratio of ammonia water to vinyl triethoxysiloxane is (1.2-10): (0.45-3.75); The polystyrene-silica core-shell microspheres are dispersed in an ethanol solvent, and then the polystyrene-silica core-shell nano-microspheres are assembled into neat face-centered cubic three-dimensional PS-SiO2 photonic crystals by self-assembly through evaporation of the ethanol solvent. (2) tetraethyl orthosilicate is autonomously nucleated and grown at room temperature under the action of ammonia water to obtain solid silica nanostructured microspheres; the particle size of the solid silica nanostructured microspheres is 180-260 nm, and the particle size is controlled by changing the volume ratio of ammonia water to tetraethyl orthosilicate, and the volume ratio of ammonia water to tetraethyl orthosilicate is (4-7.5):20; The solid silica nanostructured microspheres are dispersed in an ethanol solvent, and then the ethanol solvent is evaporated to self-assemble the solid silica nanostructured microspheres into a three-dimensional SiO2 photonic crystal with neat face-centered cubic stacking; (3) calcining the three-dimensional PS-SiO2 photonic crystal obtained in step (1) at 500-600° C. in a muffle furnace for 8-12 h to obtain a hollow SiO2 photonic crystal; filling the prepolymer monomer added with a photoinitiator into the hollow SiO2 photonic crystal, curing by ultraviolet exposure, embedding and combining the prepolymer monomer and the hollow SiO2 photonic crystal, and peeling off the obtained polymer film to obtain a hollow SiO2 structural color gel; (4) filling the prepolymer monomer added with a photoinitiator into the three-dimensional SiO2 photonic crystal obtained in step (2), curing by ultraviolet exposure, inlaying and combining the prepolymer monomer and the three-dimensional SiO2 photonic crystal, peeling off the obtained polymer film, and etching SiO2 with hydrofluoric acid having a volume percentage concentration of 4% to obtain an inverse opal gel; (5) The hollow SiO2 structural color gel obtained in step (3) and the inverse opal gel obtained in step (4) are stacked together in two layers, and bonded under ultraviolet light using ethoxylated trimethylolpropane triacrylate and a photoinitiator in a mass ratio of 99:1 to obtain a double-layer hollow structure photonic gel film with controllable water permeability and color change.

2. The method for preparing a double-layer hollow structure photonic gel film with controllable water permeation and color change according to claim 1, characterized in that: The initiator in step (1) is potassium persulfate or ammonium persulfate.

3. The method for preparing a double-layer hollow photonic gel film with controllable water permeation and color change according to claim 1, characterized in that: The calcination time in step (2) is 550° C. and the calcination time is 12 hours.

4. The method for preparing a double-layer hollow photonic gel film with controllable water permeation and color change according to claim 1, characterized in that: The prepolymer monomers in step (3) and step (4) are composed of a polymer monomer and a cross-linking agent in a mass ratio of 1:1 to 1:2, wherein the polymer monomer is one or more of acrylic acid, hydroxyethyl methacrylate, polyethylene glycol diacrylate and methyl acrylate; and the cross-linking agent is ethoxylated trimethylolpropane triacrylate.

5. The method for preparing a double-layer hollow structure photonic gel film with controllable water permeation and color change according to claim 4, characterized in that: The prepolymer liquid monomers include acrylic acid, polyethanol diacrylate and ethoxylated trimethylolpropane triacrylate in a mass ratio of 1:4:5 to 1:4:

10.

6. The method for preparing a double-layer hollow structure photonic gel film with controllable water permeation and color change according to claim 1, characterized in that: The photoinitiator in step (3) and step (4) is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the amount of the photoinitiator used is 2% to 3% of the mass of the polymer monomer in the prepolymer liquid monomer.

7. A photonic gel film with a double-layer hollow structure and controllable water permeation and color change, prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the double-layer hollow structure photonic gel film with controllable water permeation and color change according to claim 7 in a signal indicator for snowmelt warning at a large ski resort, a portable alcohol solubility detector, or an anti-counterfeiting identification label for small commercial packaging.

Citation Information

Patent Citations

  • Blue-green hollow monox photonic crystal structural color film and preparing method thereof

    CN105439461A

  • Purple hollow silicon oxide photonic crystal structure color thin film and preparation method thereof

    CN105439462A

  • Chromogenic double inverse opals photonic crystal resin film using water as ink and the preparation thereof

    US20230183407A1

  • A composition comprising a dispersion of photonic particles; methods of treating various materials

    WO2011045746A2